Edward Said on orientalism - Said, Edward W.; Jhally, Sut; Talreja, Sanjay; Media Education Foundation (Northampton, MA : Media Education Foundation, 2002)
Edward Said's book Orientalism has been influential in a diverse range of disciplines since its publication in 1978. In this interview he talks about the context in which the book was conceived, its main themes, and how its original thesis relates to the contemporary understanding of'the Orient'
Originally produced in VHS in 1998
Keywords: Said, Edward W; East and West; Imperialism; Asia -- Foreign public opinion, Occidental; Middle East -- Foreign public opinion, Occidental